Media Optimization of Student Learning Outcomes Evaluation based on Whatsapp Robot in Health Department of Jember State Polytechnic - Riskha Dora Candra Dewi (International Journal of Social Service and Research, 2022)
Online learning (e-learning) and conventional or classical learning tend to have the same effectiveness, but online learning has advantages in terms of flexibility. In carrying out their duties and functions, the researcher found that the evaluation system for student learning outcomes at the Jember State Polytechnic Health Department was not optimal. Thus, the study aims to describe the evaluation system for student learning outcomes based on WhatsApp Chatbot. Optimizing the evaluation of student learning outcomes has 8 stages, namely identifying problems through student respondent surveys, studying literature and supporting data for the manufacture of whatsapp robots, planning the process of making an evaluation system for student learning outcomes based on whatsapp robots, conducting a needs analysis of the whatsapp-based student learning outcomes evaluation system. Robots, designing systems, making media for evaluating student learning outcomes based on whatsapp robots, validating the system made by conducting trials and holding a Forum Group Discussion (FGD) for its use. In general, the optimization of the media for evaluating student learning outcomes with the WhatsApp robot-based application went well. However, this can continue to be developed, especially during the current covid-19 pandemic, some suggestions for the perfection of this application can hopefully be followed up as learning media innovations and evaluating student learning outcomes.